Steric hindrance and electronic effects of sulfonatepropyl chain on gold center. An experimental and DFT study - Fernandez, Gabriela Araceli (2017)
Density Functional Theories (DFT) methods were applied to describe the catalytic effect of a series of sulfonated NHC gold(I) complexes In order to explain the experimental results obtained in the hydration of phenylacetylene in aqueous media. The complexes [1,3-bis(2,6-diisopropyl-4-sodiumsulfonatophenyl)imidazol-2-ylidene]gold(I) chloride (C1) and [(3-sulfonatepropyl)imidazol-2-ylidene]gold(I) chloride (C5) were considered representative compounds based on their structure and reactivity. In accordance to the experimental results, the DFT studies show that the alkyl chain folds generate a strong steric hindrance and electronic effects on the metal center causing a decrease of the catalytic activity.